Effects of altitude on meat quality difference and its relationship with HIF‐1α during postmortem maturation of beef. Issue 12 (26th October 2022) - Xin, Keqi; Tian, Kai; Yu, Qunli; Han, Ling; Zang, Zhixuan
Abstract: This study investigated the differences in meat quality during postmortem aging of yak meat from different altitudes as well as the relationship between the release of hypoxic factor HIF‐1α and meat quality. The results showed that the HIF‐1α increased with altitude but during aging process, there was an initial increase before a subsequent decrease ( p  < .05). Moreover, significant increases were showed in glycolytic potential, a* value, pH, HIF‐1α mRNA expression, HIF‐1α protein expression and shear force with altitude ( p  < .05). Additionally, the b* value, L* value, water holding power and MFI decreased significantly ( p  < .05). HIF‐1α was shown, by PLS‐DA method analysis, to be the main protein marker for differences in the quality during aging time of meat from three altitude groups. HIF‐1α protein expression was high correlated with glycolytic potential, pH value, meat color, tenderness and water holding capacity during postmortem aging. The results demonstrated that HIF‐1α is a novel marker protein that influences meat quality in yak from different altitudes and that HIF‐1α‐mediated glycolytic pathway was key to the meat quality during postmortem aging. Practical applications: Yak meat has the advantages of high protein, low fat, good amino acid and fatty acid composition, so the nutritional value of yak meat is in line with the current best‐selling beef with less fat in domestic and foreign markets. But consumers often think that the meat tenderness of yak meat is worse than that of beef and improving the quality of yak meat was worthy of attention specifically. This study investigated the differences in meat quality during postmortem aging of yak meat at different altitudes and the relationship between hypoxic factor HIF‐1α release and meat quality. Abstract : This study investigated the differences in meat quality during postmortem aging of yak meat at different altitudes and the relationship between hypoxic factor HIF‐1α release and meat quality. As Journal of Food Biochemistry has a long‐standing interest in publishing research related to the meat quality field, we feel your readership will be interested in this study that contributes to further understanding changes in meat quality during aging.